2003
DOI: 10.1165/rcmb.2002-0235oc
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Prevents Apoptosis through Inhibition of Caspase Activation and Induces Necrosis

Abstract: Emphysema is characterized by enlargement of the distal airspaces in the lungs due to destruction of alveolar walls. Alveolar endothelial and epithelial cell apoptosis induced by cigarette smoke is thought to be a possible mechanism for this cell loss. In contrast, our studies show that cigarette smoke condensate (CSC) induces necrosis in alveolar epithelial cells and human umbilical vein endothelial cells. Furthermore, study of the cell death pathway in a model system using Jurkat cells revealed that in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
79
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 52 publications
10
79
1
2
Order By: Relevance
“…Although this finding supports the notion that necrosis rather than apoptosis is the usual death mode of structural cells [15], it must not be forgotten that apoptosis of structural cells occurs more frequently in more chronic situations. The study also found numerous apoptotic neutrophils and neutrophils in the process of secondary necrosis, suggesting that the apoptotic process is not too swift to be detected.…”
Section: Discussionsupporting
confidence: 70%
“…Although this finding supports the notion that necrosis rather than apoptosis is the usual death mode of structural cells [15], it must not be forgotten that apoptosis of structural cells occurs more frequently in more chronic situations. The study also found numerous apoptotic neutrophils and neutrophils in the process of secondary necrosis, suggesting that the apoptotic process is not too swift to be detected.…”
Section: Discussionsupporting
confidence: 70%
“…We found in this study that ECS exposure of larval ‰ies decreased the level of total glutathione (that is, GSH plus GSSG) in the bodies of all four strains examined. According to Wickenden and colleagues, who observed in cultured human cells that the total glutathione decreased following treatment with cigarette smoke condensate, GSH may conjugate with cigarette smoke components, as GSH is utilized in living cells in detoxiˆcation processes by forming conjugates with xenobiotics (31). This interpretation could also be applied to the present data.…”
Section: Discussionsupporting
confidence: 61%
“…These cells secrete inflammatory cytokines, proteases, and reactive oxygen species, causing necrosis, tissue damage, and further amplification of the inflammatory response with enhanced recruitment of neutrophils into the lung. Tissue damage promotes the release of inflammatory mediators and inhibits lung tissue repair functions, further increasing the tissue damage in the lungs of smokers (35,38,39). It is generally accepted, although it has not been formally proven, that these alterations could allow access of microorganisms to the otherwise sterile lungs, thereby leading to microbial colonization (28)(29)(30).…”
mentioning
confidence: 99%